Value-Based Organizational Commitment In Improving Human Resources Performance In Higher Education - Samsul Maarif (Program Studi Manajemen Pendidikan Islam UIN Sunan Ampel Surabaya, 2023)
This study aims to reveal value-based organizational commitment in senior tertiary institutions in East Java, namely University Pesantren Tinggi Darul Ulum Jombang and Sunan Giri University Surabaya. From the various data obtained by researchers, it was found that the two tertiary institutions had each attempted to increase value-based organizational commitment. Organizational commitment is an attitude, the determination of employees who have the desire to show membership behavior or an attitude that reflects loyalty, employee loyalty to their organization on an ongoing basis where members of the organization express their concern for the organization, which includes; a) a strong desire to maintain membership in the organization, b) a desire to encourage various efforts so that the organization has a high level, c) trustworthiness and acceptance of the goals and culture of the organization.